1967
DOI: 10.1002/jmor.1051220406
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of developing bristles in wild type and mutant Drosophila melanogaster

Abstract: In an attempt to understand the factors involved in morphogenesis of a complex cell like a scale or bristle, the fine structure of the normal development of bristle cells in Drosophila melanogaster (Oregon R ) has been studied and compared with that of the mutants sn3 and Sb. In the development of the normal bristle rounded bundles of longitudinally oriented fibrils lie just beneath the cell surface at regularly spaced intervals. Fiber bundles constitute about 20% of the cross sectional area. The cytoplasmic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 16 publications
2
68
1
Order By: Relevance
“…Development (2014) cells (Cant et al, 1994), dendrite terminal branchlets in sensory neurons (Nagel et al, 2012), actin bundles in the bristles (Cant et al, 1994;Overton, 1967;Tilney et al, 1995) or lamellae microspikes in plasmatocytes (Zanet et al, 2009). In these structures sn promotes the formation of straight and stiff structures, whereas its absence leads to the formation of curved ones.…”
Section: Research Articlementioning
confidence: 99%
“…Development (2014) cells (Cant et al, 1994), dendrite terminal branchlets in sensory neurons (Nagel et al, 2012), actin bundles in the bristles (Cant et al, 1994;Overton, 1967;Tilney et al, 1995) or lamellae microspikes in plasmatocytes (Zanet et al, 2009). In these structures sn promotes the formation of straight and stiff structures, whereas its absence leads to the formation of curved ones.…”
Section: Research Articlementioning
confidence: 99%
“…During pupal development, the bristle cell elaborates a long process that contains prominent longitudinal bundles of actin filaments associated with the plasma membrane (Overton, 1967;Appel et al, 1993). Cuticle is deposited on the surface of this process, and then as development proceeds, the actin cytoskeleton disassembles, the cell regresses, and the remaining hollow tube of cuticle becomes the adult bristle.…”
Section: Introductionmentioning
confidence: 99%
“…The more consistent and severe phenotype may require the constant and abundant presence of the truncated protein in bristles as suggested by the difference in bristle phenotype between Sb 1 , in which the truncated Sb 1 transcript is expressed in amounts comparable to the wild-type transcript, and Sb 63b , in which the similarly truncated transcript is overexpressed compared to the wild-type transcript. Sb 1 bristles are longer than those of Sb 63b and while Sb 1 bristles often have extra actin bundles, the number of bundles (11-18) overlaps with that of wild type (Lees and Picken 1945;Overton 1967).…”
Section: /Sbdmentioning
confidence: 94%
“…We propose that ECM constraint is an additional external force in bristle morphogenesis. Lees and Picken (1945), Overton (1967), and Tilney et al (2003) all found that the total bristle volume is the same in wild-type and Sb mutants; the increased bundle number and thickness in the mutants corresponds to the decrease in length. The extra bundles are most numerous in severe dominant mutants that produce a truncated protein entirely lacking the stubblin protease, e.g., Sb 63b (Appel et al 1993).…”
mentioning
confidence: 86%
See 1 more Smart Citation